Bulk Comptonization: new hints from the luminous blazar 4C+25.05. (5th October 2017) - Kammoun, E. S.; Nardini, E.; Risaliti, G.; Ghisellini, G.; Behar, E.; Celotti, A.
Abstract: Blazars are often characterized by a spectral break at soft X-rays, whose origin is still debated. While most sources show a flattening, some exhibit a blackbody-like soft excess with temperatures of the order of ∼0.1 keV, similar to low-luminosity, non-jetted Seyferts. Here, we present the analysis of the simultaneous XMM–Newton and NuSTAR observations of the luminous flat-spectrum radio quasar 4C+25.05 ( z = 2.368). The observed 0.3–30 keV spectrum is best described by the sum of a hard X-ray power law ($Γ = 1.38_{-0.03}^{+0.05}$ ) and a soft component, approximated by a blackbody with $kT_{\rm BB} = 0.66_{-0.04}^{+0.05}$ keV (rest frame). If the spectrum of 4C+25.05 is interpreted in the context of bulk Comptonization by cold electrons of broad-line region photons emitted in the direction of the jet, such an unusual temperature implies a bulk Lorentz factor of the jet of Γbulk ∼ 11.7. Bulk Comptonization is expected to be ubiquitous on physical grounds, yet no clear signature of it has been found so far, possibly due to its transient nature and the lack of high-quality, broad-band X-ray spectra.